2023
DOI: 10.3390/ijms241310798
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lncRNAs Deregulated in Epithelial Ovarian Cancer Based on a Gene Expression Profiling Meta-Analysis

Abstract: Epithelial ovarian cancer (EOC) is one of the deadliest gynecological cancers worldwide, mainly because of its initially asymptomatic nature and consequently late diagnosis. Long non-coding RNAs (lncRNA) are non-coding transcripts of more than 200 nucleotides, whose deregulation is involved in pathologies such as EOC, and are therefore envisaged as future biomarkers. We present a meta-analysis of available gene expression profiling (microarray and RNA sequencing) studies from EOC patients to identify lncRNA ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 308 publications
(181 reference statements)
0
1
0
Order By: Relevance
“…Additionally, cell-specific and tissue-specific expression patterns are distinctive features of lncRNAs ( 29 ), facilitating the identification of lesions in specific tissues and the classification of different cell types ( 30 , 31 ). Surprisingly, there was an unexpected specificity between dysregulated lncRNAs and histological isoforms of OC ( 32 ). Therefore, the exploration of the tissue specificity of lncRNAs will help to discover new markers associated with cancer types and apply them to the early detection of tumors or anti-cancer therapy.…”
Section: Overview Of Lncrnamentioning
confidence: 99%
“…Additionally, cell-specific and tissue-specific expression patterns are distinctive features of lncRNAs ( 29 ), facilitating the identification of lesions in specific tissues and the classification of different cell types ( 30 , 31 ). Surprisingly, there was an unexpected specificity between dysregulated lncRNAs and histological isoforms of OC ( 32 ). Therefore, the exploration of the tissue specificity of lncRNAs will help to discover new markers associated with cancer types and apply them to the early detection of tumors or anti-cancer therapy.…”
Section: Overview Of Lncrnamentioning
confidence: 99%
“…With the development of human genome sequencing technologies, various nonprotein-coding transcripts have been discovered. Those transcripts with more than 200 nucleotides in length are termed long noncoding RNAs (lncRNAs) [ 4 ] . It has been widely reported that lncRNAs participate in multiple biological processes, including the regulation of transcriptional and posttranscriptional gene expression.…”
Section: Introductionmentioning
confidence: 99%